2007
DOI: 10.1093/jxb/erl272
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive development and phenotypic differences in garlic are associated with expression and splicing of LEAFY homologue gaLFY

Abstract: Modern garlic (Allium sativum L.) cultivars are sterile and propagated only vegetatively. The recent discovery of fertile genotypes in Central Asia and the restoration of flowering and fertility by environmental manipulations open the way for in-depth florogenetic, genetic, and molecular research in garlic. In the present work, two bolting garlic accessions were employed: #3026, developing normal flowers and seeds, and #2509, in which flowers abort at the early stages of development. Morphological studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Application of comparative genomics will further allow the transfer of knowledge from thoroughly studied model plants to yam. Discovery of genes involved in flowering in model plants such as Arabidopsis have been successfully utilized to identify homologous genes in garlic (Rotem et al 2007) and in cauliflower (Saddic et al 2006). Such approaches can be adopted for discovery of genes regulating the flowering signaling pathways in yam.…”
Section: Identification Of Candidate Genes By Comparative Genomicsmentioning
confidence: 99%
“…Application of comparative genomics will further allow the transfer of knowledge from thoroughly studied model plants to yam. Discovery of genes involved in flowering in model plants such as Arabidopsis have been successfully utilized to identify homologous genes in garlic (Rotem et al 2007) and in cauliflower (Saddic et al 2006). Such approaches can be adopted for discovery of genes regulating the flowering signaling pathways in yam.…”
Section: Identification Of Candidate Genes By Comparative Genomicsmentioning
confidence: 99%
“…gaLFY expression patterns were analyzed by quantitative real-time PCR (qPCR) and RNA in situ hybridization, using primers and probes designed from the formerly described 682-bp fragment of the gene (Rotem et al 2007; GenBank AY563104 http://www.ncbi.nlm.nih.gov/nuccore/ 48476628).…”
Section: Rna Isolation and Cdna Preparationmentioning
confidence: 99%
“…Recently, we have demonstrated that the LFY homologue gaLFY is involved in the control of florogenesis in garlic. Further, we showed that two alternatively spliced gaLFY transcripts are expressed in flowering garlic plants (Rotem et al 2007). …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations